2018
DOI: 10.5565/rev/tradumatica.198
|View full text |Cite
|
Sign up to set email alerts
|

对译后编辑人员特点和实践的思考。

Abstract: The objective of this paper is to share results of the online survey Post-Editing in Action conducted among language experts currently engaged in the MTPE industry. By filling in an online questionnaire the respondents shared information concerning their professional profiles and day-to-day working routines. The survey outcomes give a richer understanding of the common tendencies -e.g. the use of PE mostly for highquality content -and provide information for tailoring translator training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Although the results are hard to compare due to different scopes and target groups of conducted research, the findings of this study are in line with those of previous research targeting multiple countries worldwide. A survey by Blagodarna (2018) has addressed 26 countries, including Lithuania, and found that the frequency of performing post-editing was varied between "never" to "very often" but a tendency was noticed for the answer "sometimes" to prevail. In our case, freelancers were more prone to do post-editing than language service providers (i.e., companies) on a day to day basis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results are hard to compare due to different scopes and target groups of conducted research, the findings of this study are in line with those of previous research targeting multiple countries worldwide. A survey by Blagodarna (2018) has addressed 26 countries, including Lithuania, and found that the frequency of performing post-editing was varied between "never" to "very often" but a tendency was noticed for the answer "sometimes" to prevail. In our case, freelancers were more prone to do post-editing than language service providers (i.e., companies) on a day to day basis.…”
Section: Discussionmentioning
confidence: 99%
“…In the extensive literature on the subject of translators' attitudes towards MTPE (Blagodarna 2018;Cadwell et al 2018;Ginovart et al 2020;Ragni and Vieira 2022;Vieira 2018;Teixiera and O'Brien 2018, among others) there is little mention of how translators perceive MTPE guidelines or how these affect the way the task is performed. Factors affecting attitudes refer to price, productivity, effort or cognitive load, but guidelines are seldom mentioned.…”
Section: Translators' Expectations Towards Mtpe Guidelinesmentioning
confidence: 99%
“…Ever since Google's introduction of neural Machine Translation (MT) in 2016 [Wu et al, 2016], we have seen an increase in the quality of MT solutions and a wider acceptance of its use by both the general population globally and the translation industry [Blagodarna, 2018]. As was to be expected, these developments have also had a considerable effect on translator training programmes.…”
Section: Introductionmentioning
confidence: 99%